PEMETAAN POTENSI LAHAN SAWAH DI KECAMATAN RATAHAN DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Febriyanto Pinoa; Sandra E. Pakasi; Zetly Tamod; Jeanne Lengkong (COCOS, 2015)
ABSTRACT The objective of this research is to map the potential of wetland in Ratahan District by using Geographic Information System. This research used Information System uses descriptive method that consists of survey in field and the overlay of map. This research implemented in the Ratahan District used Citra satellite and physical observations in the field to see the areas that have the potential in wetland with the help of a 5 point coordinate. Mapmaking conducted at the Laboratory of Remote Sensing and GIS Soil Department, Faculty of Agriculture, University of Sam Ratulangi for two months (February-March) The potential of wetland in Ratahan District covering 6216.73 ha comprising: The potential of wetland on the slope of 0-8% covering an area of 5,850 ha, which is in the conversion of land use people's plantation area of 4467.00 ha, shrubs covering 448.00 ha, moor area of 444.00 ha and use of wetland is currently an area of 451.00 ha. The potential spread of paddy fields in Maulit village, Poniki village, Rasi village, Wioi village, Ratahan village, Pangu village, Tosiraya village, Vice Mayor village and Vice Mayor Pasan village. The potential of wetland at slope > 8% area of 366.73 ha is in the conversion of land use people's plantation area of 191.81 ha and use of wetland currently 174.92 ha. The potential of wetland in Kalatin spread in the village, and Lowu village. Keywords: Wetland, Geographic Information System.